Strategies for Teaching Junior High School English Grammar Based on Thematic Contexts - Zeng, Ruirui (Scientific Journal of Technology, 2025)
This paper focuses on junior high school English grammar teaching. Considering the numerous problems in traditional grammar teaching methods, exploring teaching strategies based on thematic contexts is of great significance. By analyzing the current teaching difficulties, it elaborates that teaching based on thematic contexts is helpful for improving students’ language application abilities and emphasizes its crucial role in language learning. The strategies include designing thematic contexts closely related to life, using multimodal resources, and conducting in-depth analysis of grammar points within contexts. For example, using "My Day" to teach the present continuous tense and using animated videos to teach verb tenses. Finally, it points out that this teaching transformation is beneficial for enhancing students’ abilities, but there are also challenges such as how to design contexts and balance knowledge and application. Teachers need to continuously explore and improve grammar teaching strategies.